(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper examines the methodological approaches and practical role of internal audit in ensuring the reliability of corporate accounting and financial reporting. It analyzes key procedures such as documentary verification, analytical reviews, and compliance checks used to identify discrepancies, errors, and information risks. Through case studies of companies like "NAVIGUL" LLC and "CHUST AGRO FRUITS" LLC, the study demonstrates how internal audit detects material misstatements in areas such as inventory valuation, revenue recognition, and depreciation calculation, which directly impact financial results and tax liabilities. The findings underscore that a systematic internal audit function not only serves a detective role but also provides a foundation for corrective actions and strategic decision-making. Furthermore, the integration of audit findings and recommendations into the company’s ongoing information systems and management processes is highlighted as a critical factor for enhancing financial transparency, reducing risks, and improving overall operational profitability.